Environmental Inequalities in Kathmandu, Nepal—Household Perceptions of Changes Between 2013 and 2021 - Flacke, Johannes; Maharjan, Basundhara; Shrestha, Rehana; Martinez, Javier (Frontiers in Sustainable Cities, 2022)
Environmental health inequalities in cities of the Global South are hardly studied up to now, though they are expected to increase due to rapid urbanization and motorization taking place in many of these cities. In this study, environmental inequalities in the city of Kathmandu, Nepal, and their changes between 2013 and 2021 are analyzed. Goal of the study is to determine the degree of environmental inequalities and its changes over time as well as drivers of change and actions taken by governmental authorities and citizens. The study examines horizontal and vertical inequalities in access to drinking water sources, exposure to air and noise pollution, and health effects based on self-reported household data. Results show statistically significant environmental inequalities between neighborhoods in Kathmandu regarding access to basic water infrastructure, air and noise pollution exposure and resulting health effects. In contrast, inequalities between socio-economic groups are not significant. Over time, the perceived exposure particularly to air pollution has increased, mainly due to increase of motorized traffic, and spatial inequalities persisted. While inequalities between socio-economic groups have not increased, the high socio-economic group reveals more concerns and awareness about environmental burdens than the low socio-economic group. In conclusion, given the intertwined horizontal and vertical inequalities, any planning response action needs to consider the population's vulnerability to target interventions to the most affected areas.